2002
DOI: 10.1093/jn/132.12.3616
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Regulation of β,β-Carotene 15,15′-Monooxygenase by Retinoic Acid in Rats and Chickens

Abstract: beta,beta-Carotene 15,15'-monooxygenase (formerly termed beta,beta-carotene 15,15'-dioxygenase, EC 1.13.11.21) catalyzes the conversion of provitamin A carotenoids to retinal in vertebrate tissues. In the present study, we investigated whether preformed vitamin A or beta-carotene and its direct metabolites can regulate the enzyme activity in vivo. We found dose-dependent decreases in intestinal beta,beta-carotene monooxygenase activity after oral administration to rats of retinyl acetate (up to -79%), beta-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…Feedback mechanisms have previously been demonstrated for RA-treatment induced down-regulation of Bco-1 expression in chickens and rats (Bachmann, et al, 2002). In the mouse testis, a strong down-regulation of Bco-1…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Feedback mechanisms have previously been demonstrated for RA-treatment induced down-regulation of Bco-1 expression in chickens and rats (Bachmann, et al, 2002). In the mouse testis, a strong down-regulation of Bco-1…”
Section: Discussionmentioning
confidence: 87%
“…It is known that BCO1 and BCO2 are tissue specifically expressed to facilitate the retinoid signaling. It has been previously demonstrated that RA down-regulates the BCO1 mRNA level in chickens and rats (Bachmann, et al, 2002). A study by Zaripheh et al showed that lycopene is the inhibitor of BCO1 as well .…”
Section: Lycopene Metabolismmentioning
confidence: 95%
“…BCM expression is inversely regulated by retinoic acid in rats with vitamin A deficiency (25). Bachmann and colleagues reported that BCM expression in the chicken intestine is under feedback regulation by retinoic acid and that BCM activity is down-regulated in the rat intestine (27). These studies indicate that retinoic acid may repress BCM gene expression in the principal tissues for retinol metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 45% of the western population can be classified as low converter [30,47]. It has been established that conversion efficiency is depending at least in part on the vitamin A status [57], which is explained by the existence of a negative feedback of RA on BCMO1 mRNA expression [3,66]. Besides, many studies have highlighted the huge interindividual variability in conversion efficiency, with a coefficient of variation being as high as 221% [7,12,30,47].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%